COMPARING CUSTOMER RELATIONSHIP QUALITY BETWEEN MALE AND FEMALE CUSTOMER OF THE PREMIERE XXI MANADO TOWN SQUARE - The, Felicia Lianna; Lapian, S.L.H.V. Joyce; Rumokoy, Farlane S (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract : The Premiere XXI Manado Town Square is facility offered by cinema XXI if the visitors want to watch a different way and luxurious facilities with ticket prices more expensive than the regular ticket price. With that conditions researcher want to help The Premiere XXI Manado Town Square to see is there any significant different in customer relationship quality which is Service Quality, Customer Satisfaction, Trust and Commitment between male and female customers or not. The researcher analyzes data based on primary data and secondary data. Primary data is collected by distributing 100 questionnaires to 50 male and 50 female customers who have ever visited and using The Premiere XXI Manado Town Square facilities more than twice. Secondary data is collected by reading books, journal and internet. The researcher uses Independent Sample T-test. By using Independent sample T-test the result shows that there is no significant difference between Male and Female Customer in Relationship Quality. Based on the results, the data is normally distributed and homogenous. The researcher recommends for The Premiere XXI Manado Town Square no need to make a different strategy for Relationship quality.. Keywoards: Relationship Quality, Service Quality, Customer Satisfaction, Trust, Commitment, Independent Sample T-test, Gender, Cinema